Drivers of Health in sub-Saharan Africa: A Dynamic Panel Analysis - Mwimba Chewe; Peter Hangoma (Elsevier, 2020)
Globally, life expectancy increased while infant mortality reduced substantially between the 19th and late 20th century. Although there is relatively mature literature on the drivers behind these gains in life expectancy and reductions in infant mortality, there is a dearth of studies that focus on the drivers of health in sub-Saharan African (SSA) countries. The few studies that do exist do not account for a broader array of determinants such as the quality of access to health services and institutional quality which may have important implications for health policy. We contribute in filling this gap by estimating the effect of a rich set of socio-economic, environmental, health system and lifestyle factors on life expectancy and infant mortality using a panel of 30 sub-Saharan African countries. We employ a dynamic Generalized Method of Moments (GMM) estimator and focus on the period between 1995-2014.Our findings show that increases in health expenditure, educational attainment, and health care access quality are associated with increases in life expectancy and reductions in infant mortality. Higher HIV prevalence rates are associated with reductions in life expectancy whereas urbanization, per capita income growth and access to clean water are positively associated with life expectancy.We conclude that increases in life expectancy and reductions in infant mortality can be accelerated by paying particular attention to interventions linked to these drivers, including, health care access quality.